Barefooted vs with footwear: functional mobility assessment on community dwelling elders - Dave, Dhruv; Vashi, Payal (International Journal Of Community Medicine And Public Health, 2019)
Background: Affected balance, restricted mobility and probability of fall is more common in elder. Most of the geriatric individuals prefer walking independently as one of the prime function, so maintenances of that even with affecting factors of fall it is essential. Footwear is one extrinsic factor which may affects postural stability and increase risk of fall. Methods: A cross sectional study conducted among community dwelling elders. Participants (n=40) have performed time up and go test (TUG) and ten meter walk test (TMW) in or out of the house with barefoot and two different type of pre-screened footwear. Descriptive statistics were done and ANOVA was performed. Results: The calculated F ratio (0.7817), (1.3100) is lesser than the table F ratio (3.0737), (3.0737) for the TMW and even For TUG so the TUG score for barefoot and two different type of footwear do not differ significantly. Conclusions: Functional mobility is not influenced by routine footwear. Barefooted and with footwear dynamic balance and gait speed is not significantly different from each other.